The Physiological and Evolutionary Ecology of Sperm Thermal Performance - Wang, Wayne Wen-Yeu; Gunderson, Alex R. (Frontiers in Physiology, 2022)
Ongoing anthropogenic climate change has increased attention on the ecological and evolutionary consequences of thermal variation. Most research in this field has focused on the physiology and behavior of diploid whole organisms. The thermal performance of haploid gamete stages directly tied to reproductive success has received comparatively little attention, especially in the context of the evolutionary ecology of wild (i.e., not domesticated) organisms. Here, we review evidence for the effects of temperature on sperm phenotypes, emphasizing data from wild organisms whenever possible. We find that temperature effects on sperm are pervasive, and that above normal temperatures in particular are detrimental. That said, there is evidence that sperm traits can evolve adaptively in response to temperature change, and that adaptive phenotypic plasticity in sperm traits is also possible. We place results in the context of thermal performance curves, and encourage this framework to be used as a guide for experimental design to maximize ecological relevance as well as the comparability of results across studies. We also highlight gaps in our understanding of sperm thermal performance that require attention to more fully understand thermal adaptation and the consequences of global change.